The Development of Web-based Instructional Media for Teaching Wave Physics on Android Mobile - Bintang Ronauli Simanjuntak; Desnita Desnita; Esmar Budi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
This study aims to develop an Android app to support learning activities consisting of mobile applications and web server applications. Mobile applications have two applications: teacher apps and student applications, while web server applications are used by teachers and administrators. Mobile apps run on Android smartphones, while web server applications are in Chrome web browsers. In mobile applications, students can view material with pictures and videos, do online tests, perform tasks, view simulations, view announcements in the form of updates made by teachers, and see recap test scores, assignments, exams, and final score in a chapter. In a mobile application, the teacher can see how many times students access the material, view the student's time notice in performing tests and tasks, view the test scores, duties, exams and the final grade of each student who is registered on the web server. Administrator applications on the web server focus more on managing the data that will changes. This application can run on Android operating system Jelly Bean and above. The development used refers to the ADDIE model with the following stages: 1) Analysis, 2) Design (design / design), 3) Development (development), and 4) Evaluation (evaluation / feedback). The developed media has been validated by subject experts, media experts and high school physics teachers with average percentage of all aspects of subject experts is 85.50%, media experts 85.20% and physics teachers 90%, based on these results show that mobile learning android platform based on web service proper to use as a media of physics learning.